1000 year-long summer precipitation and flood frequency record for the North-western Alps (Lake Oeschinen) - Benjamin Amann; Sönke Szidat; Martin Grosjean (PANGAEA, 2018)
The recent warming of the global climate is well recognized. However, does a warmer climate also mean a moister climate? Does dry get drier and wet get wetter? There are important questions as they relate to changes in the water cycle and impacts the water resources as well as the frequency and intensity of storms and floods in the near future. In Europe, regional climate models do not show consistent and robust results for future hydroclimatic changes and how extreme events will evolve in response to future climate change. Paleo-hydroclimatic data from natural archives are one of the few means to assess such changes in the longer context. Here, we present an annually-resolved record of warm season (MJJA) precipitation and summer flood frequency from the varved (annually laminated) sediments of proglacial Lake Oeschinen (46°30'N–7°44'E, 1580 m, NW Swiss Alps) back to AD 884. These data sets are inferred from the thickness of annual sediment deposits and the occurrence of flood event layers in the sediments. The chronology of the sediment record is based on multiple varve counts and validated with historical floods chronicled in written documents (back to the 14th century) and 14C AMS dates.
Supplement to: Amann, B et al. (2015): A millennial-long record of warm season precipitation and flood frequency for the North-western Alps inferred from varved lake sediments: implications for the future. Quaternary Science Reviews, 115, 89-100, https://doi.org/10.1016/j.quascirev.2015.03.002